The impact of human resource strategy to knowledge process and knowledge capability towards innovation in the Malaysian electrical and electronics firms - Yousif Mamoun (2017)
he purpose of this thesis is to develop innovation within the Malaysian electrical and electronics firms. For some firms, innovation occurs only at irregular times, while some others seek to innovate continuously, but there is a lack of knowledge of the necessary steps needed to generate innovation. Thus, the research objectives investigates the impact of human resource strategy, knowledge process and knowledge capability to develop innovation in electrical and electronics firms. This thesis conducted a quantitative approach using, a questionnaire as the research tool using five points Likert scale. The respondents of this study consists of 287 managers from electrical and electronics firms across Malaysian states including Kuala Lumpur, Selangor, Penang, Johar, Kedah, Melaka, Sabah and Sarawak. The list from the Federation of Malaysian Manufacturers (FMM) indicated that most of firms were located in these states. Out of 287 questionnaires only 102 usable were received. Statistical package for social science was used to generate the descriptive statistics besides the Partial least squares structural equation modeling (PLS SEM) as the statistical instrument to examine the measurement model and structural model. Results confirmed that, human resource strategy is significant to knowledge process and knowledge capability. Also, It has been shown that a learning culture and knowledge application are significant and the most important determinants of innovation. Eventually, which contributes in the development of the Malaysian electrical and electronics firms. The confirmation of mediating effects shows that indirect effects exist, confirming the existence of the proposed relationship posited, where knowledge process and knowledge capability mediate the relationships· between human resource strategy and innovation. This thesis draws a theoretical contribution by the application of human resource strategy and knowledge process and knowledge capability to innovation in the context of Malaysian electrical and electronics firms. Therefore, this thesis expands the body of knowledge in the area of innovation because more studies are needed in this field especially in the Malaysian context also because of the importance of this sector in producing advanced products that needs high level of knowledge. Consequently, drawing upon the findings, some guidelines are suggested for top management and decision makers on how to encourage such enhancement to innovate by the application of human resource strategy that enhances the level of knowledge and skills, besides developing appropriate behavior that develops innovation. Eventually, management and decision makers would identify the necessary steps on how to encourage and generate innovation in their organizations.